The Effectiveness of the Future Time Perspective Group Guidance with Mind Mapping and Group Discussion Techniques to Improve Students’ Career Planning - Mursal, Ahmad; Sugiharto, DYP; Sugiyo, Sugiyo (Universitas Negeri Semarang, 2023)
Career is one’s whole life in form of self-realization to live and achieve goals. To do so, he must have the ability in career planning. Good career planning will enable students to determine the types of work and education they may take. In regard to this, the present study attempted to prove that the future time perspective-based group guidance with mind mapping and group discussion techniques was able to improve students’ career planning. It used an experimental method with a randomized pretest-posttest control group design and involved 21 students in grade twelve at SMA Negeri 1 OKU. Based on the Wilcoxon and Mann Whitney tests, the application of mind mapping technique in this intervention resulted better. Further implications and limitations are discussed in the discussion section.